2012
DOI: 10.1111/mmi.12076
|View full text |Cite
|
Sign up to set email alerts
|

The fungal α‐aminoadipate pathway for lysine biosynthesis requires two enzymes of the aconitase family for the isomerization of homocitrate to homoisocitrate

Abstract: Fungi produce α-aminoadipate, a precursor for penicillin and lysine via the α-aminoadipate pathway. Despite the biotechnological importance of this pathway, the essential isomerization of homocitrate via homoaconitate to homoisocitrate has hardly been studied. Therefore, we analysed the role of homoaconitases and aconitases in this isomerization. Although we confirmed an essential contribution of homoaconitases from Saccharomyces cerevisiae and Aspergillus fumigatus, these enzymes only catalysed the interconve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0
3

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(41 citation statements)
references
References 70 publications
1
37
0
3
Order By: Relevance
“…The protein sequence of CNAG_02565 is highly homologous to Lys4, an enzyme in the lysine biosynthesis pathway in S. cerevisiae , with 64% similarity and 52% identity [21]. We therefore designated CNAG_02565 as LYS4 and constructed a mutant strain lacking the gene for further characterization in C. neoformans .…”
Section: Resultsmentioning
confidence: 99%
“…The protein sequence of CNAG_02565 is highly homologous to Lys4, an enzyme in the lysine biosynthesis pathway in S. cerevisiae , with 64% similarity and 52% identity [21]. We therefore designated CNAG_02565 as LYS4 and constructed a mutant strain lacking the gene for further characterization in C. neoformans .…”
Section: Resultsmentioning
confidence: 99%
“…GC‐MS profiling revealed that the dominant metabolites and metabolic pathways in green blooms were associated with nitrogen and amino acid metabolism, and in red blooms with osmolyte and fatty acid metabolism. High on the list of compounds associated with green communities were lysine and its precursor aminoadipic acid, the latter importantly being a precursor for penicillin synthesis in fungi that produce α‐aminoadipate (Fazius et al ., ). Also dominant in the green blooms was calystegine, an alkaloid involved in plant–bacterial communication, including with Pseudomonas (a reported bacterial genus in our 16S sequencing), which is reported to catabolise it (Goldmann et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…For generating a version with an N-terminal His tag, the gene was amplified from genomic DNA of SC5314 with oligonucleotides BamHI_HPD1_ATG_f (5Ј-GGA TCC ACC AAT TAC GGG TTT ATT GG-3Ј) and NotI_HPD1_TAA_re (5Ј-GCG GCC GCT TAT TTT CTT TTG ACA TCA ATT ACA TC-3Ј), cloned in pJET1.2, and excised by BamHI ϩ NotI restriction. The fragment was subcloned in a modified pET43 vector in-frame with the His tag sequence (40,41). For generation of a version with C-terminal His tag, the gene excluding the mitochondrial import sequence and the terminal stop codon was amplified with oligonucleotides IF_pet29HPD1_f (5Ј-aag gag ata tac ata tgA CCA ATT ACG GGT TTA TTG GTT TG-3Ј; overhang in lowercase letters) and IF_pet29HPD1_r (5Ј-aca ggt ttt cgg atc cTT TTC TTT TGA CAT CAA TTA CAT CAC-3Ј; overhang in lowercase letters) and directly cloned by In-Fusion PCR cloning (Takara Bio Europe/Clontech) in an NdeI ϩ BamHI-restricted pET29a vector (Merck).…”
Section: Methodsmentioning
confidence: 99%